Evaluation of Using LaNi0.6Fe0.4O3–δ Contact Layer Between La0.6Sr0.4FeO3 Cathode and Crofer22APU Interconnect for Solid Oxide Fuel Cells. Issue 3 (22nd April 2016) - Morán‐Ruiz, A.; Vidal, K.; Larrañaga, A.; Arriortua, M. I.
Abstract: Interconnect‐cathode interfacial adhesion is important for the durability of solid oxide fuel cell (SOFC). Thus, the use of a conductive contact layer between interconnect and cathode could reduce the cell area specific resistance (ASR). The use of La0.6 Sr0.4 FeO3 (LSF) cathode, LaNi0.6 Fe0.4 O3– δ (LNF) contact layer and Crofer22APU interconnect was proposed as an alternative cathode side. LNF‐LSF powder mixtures were heated at 800 °C for 1, 000 h and at 1, 050 °C for 2 h and analyzed by X‐Ray power diffraction (XRD). The results indicated a low reactivity between the materials. The degradation occurring between the components of the half‐cell (LSF/LNF/Crofer22APU) was studied. XRD results indicated the formation of secondary phases, mainly: SrCrO4, A(B, Cr)O3 (A = La, Sr; B = Ni, Fe) and SrFe12 O19 . Scanning electron microscopy with energy dispersive X‐Ray spectroscopy (SEM‐EDX) and the X‐Ray photoelectron spectroscopy (XPS) analyzes confirmed the interaction between LSF/LNF and the metallic interconnect due to the Cr vaporization/migration. An increment of the resistance of ∼0.007 Ω cm 2 in 1, 000 h is observed for (LSF/LNF/Crofer22APU) sample. However, the ASR values of the cell without contact coating, (LSF/Crofer22APU), were higher (0.31(1) Ω cm 2 ) than those of the system with LNF coated interconnect (0.054(7) Ω cm 2 ), which makes the proposed materials combination interesting for SOFC.